1998
DOI: 10.1046/j.1469-8137.1998.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomass, reproductive output, and physiological responses of rapid‐cycling Brassica (Brassica rapa) to ozone and modified root temperature

Abstract: Brassica rapa L. (rapid-cycling Brassica), was grown in environmentally controlled chambers to determine the interactive effects of ozone (O $ ) and increased root temperature (RT) on biomass, reproductive output, and photosynthesis. Plants were grown with or without an average treatment of 63 ppb O $ . RT treatments were 13 mC (LRT) and 18 mC (HRT). Air temperatures were 25 mC\15 mC day\night for all RT treatments.Ozone affected plant biomass more than did root temperature. Plants in O $ had significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Light microscopy revealed that the reduction in g s induced by O 3 in both leaves was due to a decline in stomatal aperture, and not to a reduction in stomatal density (Table 1), so the data for leaf 10 suggest that ‘direct’ effects of O 3 on stomatal aperture may have contributed to the O 3 ‐induced decline in g s observed in the present study. This conclusion is supported by other reports of O 3 ‐induced changes in g s independent of effects on the capacity for CO 2 assimilation (Kleier et al. 1998; Torsethaugen et al 1999).…”
Section: Discussionsupporting
confidence: 89%
“…Light microscopy revealed that the reduction in g s induced by O 3 in both leaves was due to a decline in stomatal aperture, and not to a reduction in stomatal density (Table 1), so the data for leaf 10 suggest that ‘direct’ effects of O 3 on stomatal aperture may have contributed to the O 3 ‐induced decline in g s observed in the present study. This conclusion is supported by other reports of O 3 ‐induced changes in g s independent of effects on the capacity for CO 2 assimilation (Kleier et al. 1998; Torsethaugen et al 1999).…”
Section: Discussionsupporting
confidence: 89%
“…well as photoassimilates in the shoot (Fu et al, 1993;Kleier et al, 1998). We found that FW as well as DW increased (P < 0.001, data not presented) with plant age.…”
Section: Resultsmentioning
confidence: 45%
“…Because root-zone warming can hasten root reserve mobilisation, canopy development and carbon assimilation (Field et al 2009, Rogiers et al 2011b, this may alter source-sink relations within the plant later in the season with consequences for berry growth and ripening as well as for final fruit size and composition. For instance, a warm root-zone resulted in heavier fruit in canola (Kleier et al 1998) and increased yield in tomatoes (Gosselin andTrudel 1984, Hurd andGraves 1985) and oranges (Cary and Weerts 1980). There are few reports of the effect of root-zone temperature on grape composition with the exception of a set of controlled environment studies carried out in the mid-to late-1970s (Kliewer 1975, Zelleke andKliewer 1979) on Cabernet Sauvignon highlighting lower acidity in berries grown in a warm root-zone.…”
Section: Introductionmentioning
confidence: 99%